2018
DOI: 10.1074/jbc.ra118.004012
|View full text |Cite
|
Sign up to set email alerts
|

Structural analyses reveal the mechanism of inhibition of influenza virus NS1 by two antiviral compounds

Abstract: The influenza virus is a significant public health concern causing 250,000-500,000 deaths worldwide each year. Its ability to change quickly results in the potential for rapid generation of pandemic strains for which most individuals would have no antibody protection. This pandemic potential highlights the need for the continuous development of new drugs against influenza virus. As an essential component and well established virulence determinant, NS1 (nonstructural protein 1) of influenza virus is a highly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 63 publications
(74 reference statements)
1
21
0
Order By: Relevance
“…Recently, structures of free 1918 NS1 ED W187A and W187R mutants were reported (10,40). This allowed us to compare the structures of 1918 NS1 ED between the free and p85β-bound states.…”
Section: Ns1 Makes the Most Of Its Surface Area For Interactions Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, structures of free 1918 NS1 ED W187A and W187R mutants were reported (10,40). This allowed us to compare the structures of 1918 NS1 ED between the free and p85β-bound states.…”
Section: Ns1 Makes the Most Of Its Surface Area For Interactions Withmentioning
confidence: 99%
“…Nonstructural protein 1 (NS1) of IAV has attracted considerable attention because of its role as a multifunctional virulence factor during the viral infection cycle (5)(6)(7)(8). Thus, it is generally considered a potential drug target for the treatment of IAV infections (9)(10)(11). The primary functions of NS1 are to antagonize host innate immune responses (12), such as the expression of type I interferon (IFN) (13)(14)(15), and to increase viral replication (7,16,17).…”
mentioning
confidence: 99%
“…In this study, A9 and A22, small molecules that are derivatives of NSC125044, were the most promising molecules, A22 being 10 times more potent than A9. Recently, Kleinpeter and coworkers [140] continued Jablonski's research [139]. Both molecules bind to NS1-ED and, by mapping the interaction region through X-ray crystallography, it was shown that they share the same binding pocket as CPSF30, meaning that these compounds can act as inhibitors of the NS1-CPSF30 interaction.…”
Section: Experimental and In Silico Approaches Towards A New Therapeumentioning
confidence: 99%
“…Inhibition of IFN pre-mRNA was found to be mediated by the binding of viral NS1 to cellular CPSF30, thus indicating this interaction as a potential therapeutic target [400]. Peptidemediated inhibition of NS1-CPSF30 binding has been shown to limit virus replication in tissue culture [399,401,402]. However, this strategy is specific to influenza A and is yet to be tested in vivo [399].…”
Section: Protein Kinase R (Pkr) and Viral Non-structural (Ns1) Proteinmentioning
confidence: 99%